PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PEMERKOSAAN DALAM PERADILAN PIDANA - Edy Suwito; Mulyadi Aribowo (Universitas Islam Kadiri, 2019)
This study aims to determine the extent to which legal protection and obstacles faced against the victims of rape in criminal justice in Blitar district court. The context of legal protection against victims of crime (criminal act of rape) is by preventive or repressive efforts conducted by both society and law enforcement officers such as providing protection from various threats that can endanger the life of the victim. The research used is juridical normative and juridical empirical research. Research location in Blitar District Court. The materials used in literature study are data collection through literature study, and field research involves interviewing informant. Based on the result of the research, the researcher got the answer that, the legal protection against the victims of criminal act of rape in criminal court in Blitar state court still caused many difficulties in settling either at the investigation stage until the victim was present in the court, because the psychic pressure in victims questioned. This of course affects the mental / psychological development of the victims and also affects the law enforcement process itself to bring about a sense of justice for victims and society.